Peran Ekspektasi Kinerja, Ekspektasi Usaha, Pengaruh Sosial, dan Kondisi yang Mendukung terhadap Perilaku Pengguna Itqan Mobile yang Dimediasi oleh Niat Perilaku Menggunakannya - Chairia Chairia; Citra Sukmadilaga; Indri Yuliafitri (Universitas Proklamasi 45 Yogyakarta, 2020)
Baitul Maal wat Tamwil (BMT) is a sharia cooperative that is able to reach up to economic actors of Small and Medium Enterprises (SMEs). Itqan BMT members in Bandung who use Itqan Mobile are far less than the number of members who do not use them. The purpose of this study was to examine the Unified Theory of Acceptance and Use of Technology (UTAUT) on users of users and not users of Itqan Mobile on Itqan BMTs in Bandung. UTAUT is a theory that is widely adopted in studies of user acceptance of a technology. The method used in this research is regression analysis followed by path analysis. Regression analysis was carried out in two stages. The result of regression I research is that effort expectations show a positive and significant role on the behavioral intentions of members using Itqan Mobile, while performmmance expectancy, social influence, and facilitating conditions do not contribute to the behavioral intentions Itqan Mobile. The results of regression II research indicate that performance expectations and effort expectations have not role in the behavior intentions Itqan Mobile. Furthermore, the results of the study also prove that performance expectations, effort expectations, social influences, and facilitating conditions show an indirect effect on the behavior of Itqan Mobile users which is mediated by behavioral intentions of using it.